Blackberry summer - Thayne, RaeAnne (Don Mills, Ont. : HQN, 2011)
Claire Bradford needed a wake-up call. What she didn't need was a tragic car accident. As a single mom and the owner of a successful bead shop, Claire leads a predictable life in Hope's Crossing, Colorado. So what if she has no time for romance? At least, that's what she tells herself, especially when her best friend's sexy younger brother comes back to town as the new chief of police.
Keywords: Single-parent families -- Fiction; Colorado -- Fiction; Man-woman relationships -- Fiction; Love stories